Severe Periodontitis and Biomarkers of Bacterial Burden. Results From a Case-Control and Intervention Clinical Trial - Yago Leira; Yago Leira; Dimitrios Fragkiskos; Marco Orlandi; Jeanie Suvan; Luigi Nibali; Maurizio S. Tonetti; Maurizio S. Tonetti; Georgios N. Belibasakis; Nagihan Bostanci; Francesco D'Aiuto (Frontiers Media S.A., 2021)
Background and aims: Periodontitis is an inflammatory-infectious disease. Identifying markers of systemic exposure of periodontitis might be of interest to study its interaction with other conditions. Soluble triggering receptor expressed on myeloid cells 1 (sTREM-1) is upregulated during bacterial infections. Our aim was therefore to investigate whether periodontitis and its treatment are associated with bacterial endotoxin and sTREM-1.Methods: Fifty patients with severe periodontitis and 50 age-matched controls were included in a case-control study (all never smokers). A secondary analysis of a previously published intervention study was performed, in which included 69 patients with severe periodontitis were randomized to receive either intensive (IPT) or control periodontal therapy (CPT) and monitored over 6 months. Serum levels of bacterial endotoxin and sTREM-1 were determined at one time point (case-control study) and at baseline, 1 day, 1 and 6 months after periodontal treatment (intervention study).Results: Severe periodontitis was associated with elevated circulating endotoxin levels when cases (22.9 ± 2.2 EU/ml) were compared to controls (3.6 ± 0.5 EU/ml, p < 0.001) and with sTREM-1 levels (1302.6 ± 47.8 vs. 870.6 ± 62.0 pg/ml, p < 0.001). A positive correlation was observed between sTREM-1 and endotoxin levels (r = 0.4, p < 0.001). At 6 months after treatment, IPT significantly decreased serum levels of sTREM-1 compared to CPT (adjusted mean difference of 500.2 pg/ml, 95% CI: 18.9-981.4; p = 0.042). No substantial differences were noted in endotoxin levels at any time point after treatment between groups.Conclusions: Severe periodontitis is linked to increased circulating endotoxin and sTREM-1 levels and following IPT a reduction in sTREM-1 levels is observed.